Antipharyngitis Effects of Syringa oblata L. Ethanolic Extract in Acute Pharyngitis Rat Model and Anti-Inflammatory Effect of Ir-Idoids in LPS-Induced RAW 264.7 Cells. (10th December 2021) - Zhu, Wen-Bo; Su, Fa-Zhi; Sun, Yan-Ping; Yang, Bing-You; Wang, Qiu-Hong; Kuang, Hai-Xue
Abstract : Acute pharyngitis is an inflammation of the pharyngeal mucous membrane and submucous lymphoid tissues. Unsatisfactory treatment and repeated occurrences might cause chronic pharyngitis and other complications. Syringa oblata L. ( S. oblata ) is a traditional Chinese medicine that exhibited a significant therapeutic effect on various inflammatory diseases. Its commercial drug Yan Li Xiao (YLX) capsule is used as a cure for the treatment of inflammatory diseases, such as bacillary dysentery, tonsillitis, bronchitis, and acute gastroenteritis. However, studies about S. oblata relieving acute pharyngitis are rare. In this study, high-performance liquid chromatography (HPLC) was used to analyze the chemical profile of S. oblata, and the bioactive phytoconstituents were isolated and identified by nuclear magnetic resonance (NMR) and mass spectrometry. An ammonia-induced acute pharyngitis rat model was established to estimate the protective effect of S. oblata in vivo for the first time. The severity of pharyngitis was observed by appearance index and HE staining. The cytokines expression was performed by ELISA. Crucial proteins expression associated with TLR4/NF- κ B/MAPK and NLRP3 inflammasome signaling pathways were analyzed by western blotting and immunohistochemistry. Furthermore, the anti-inflammatory effect of isolated compounds was evaluated by suppressing lipopolysaccharide- (LPS-) induced NO generation and regulating the cytokines levels in RAW 264.7 cells. The results showed that S. oblata exhibited a protective effect in the ammonia-induced acute pharyngitis rat model, and the compounds exert potential anti-inflammatory properties against LPS-activated RAW 254.7 cells.